Analisis Laju Erosi Berdasarkan Kemiringan Lereng Pada Area Pasca Spreading PT Angsana Jaya Energi Tanah Bumbu Kalimantan Selatan - Dewantari, Eva Hestina; Wicaksono, Aditya Pandu (Jurnal Lingkungan Kebumian Indonesia, 2023)
The implementation of mining requires employment of protection and management of the affected environment, such as reclamation. The initial stage of reclamation in the form of spreading topsoil serves to prevent land subsidence/erosion. Post spreading area will be left empty for 1 month which causes erosion. This study aims to determine the amount of erosion rate that occurs in the spreading area based on the slope of gentle and sloped slopes and the direction of flow that occurs. The determination of the sampling point was carried out using the purposive sampling method and the measurement of the erosion rate was carried out using the stick method by sticking a stick with a depth of 30 cm with a plot size of 10x10 meters with division of 3 points on the slope of the slope and 3 points on the slope of the gentle slope. Soil sampling is carried out to measure the weight of the volume. Land subsidence measurements were carried out for 19 days for 30 days in each rain event. The calculation of the largest erosion rate on the slope of the gentle slope and the slope was 7,531.29 tons/ha/year and 7,746.44 tons/ha/year respectively which occurred on December 03, 2022., while the smallest erosion rate value on the slope of the gentle slope was on December 15, 2022 of 1,551.6 tons/ha/year and on the slope of the gentle slope was on December 1, 2023 of 1,647.1 tons/ha/year.